2021
DOI: 10.3390/jcm10051051
|View full text |Cite
|
Sign up to set email alerts
|

Arginase 1 (Arg1) as an Up-Regulated Gene in COVID-19 Patients: A Promising Marker in COVID-19 Immunopathy

Abstract: Background: The coronavirus disease 2019 (COVID-19) outbreak, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been declared a global pandemic. It is well-established that SARS-CoV-2 infection can lead to dysregulated immune responses. Arginase-1 (Arg1), which has a pivotal role in immune cells, can be expressed in most of the myeloid cells, e.g., neutrophils and macrophages. Arg1 has been associated with the suppression of antiviral immune responses. Methods: Whole blood was taken f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…4e) and CD24 (both mRNA and protein; Extended Data Fig. 6i), suggesting that additional immunomodulatory function [45][46][47][48][49] expanded with dexamethasone. Both ARG1 and ANXA1 express glucocorticoid response elements, emphasizing the possibility of their direct regulation by dexamethasone treatment 50,51 .…”
Section: Neutrophil Ifn Programs Are Restrained With Dexamethasonementioning
confidence: 99%
“…4e) and CD24 (both mRNA and protein; Extended Data Fig. 6i), suggesting that additional immunomodulatory function [45][46][47][48][49] expanded with dexamethasone. Both ARG1 and ANXA1 express glucocorticoid response elements, emphasizing the possibility of their direct regulation by dexamethasone treatment 50,51 .…”
Section: Neutrophil Ifn Programs Are Restrained With Dexamethasonementioning
confidence: 99%
“…Rees et al (12) have reported alterations in amino acid levels, including arginine and ornithine, in COVID-19 patients. Another recent paper has described increased RNA expression of Arg1 in the peripheral blood mononuclear cells of COVID-19 patients, although they did not identify the cell of origin of this Arg1 (13). Arginine depletion inhibits T cell receptor signaling resulting in T cell dysfunction (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study performed whole‐transcriptome RNA sequencing of 14 peripheral blood samples from COVID‐19 patients ( n = 10) and healthy donors ( n = 4), from which researchers screened a large number of differentially expressed mRNAs and miRNAs and constructed a lncRNA‐miRNA‐mRNA regulatory network 16 . In addition, Arg1 has recently been found to be highly expressed in the peripheral blood leukocytes of COVID‐19 patients and may be a diagnostic marker for COVID‐19 17 . These studies contribute to the understanding of gene regulatory relationships and inflammatory mechanisms in the immune cells of COVID‐19 patients and lay the foundation for the discovery of new diagnostic markers for COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, Arg1 has recently been found to be highly expressed in the peripheral blood leukocytes of COVID-19 patients and may be a diagnostic marker for COVID-19. 17 These studies contribute to the understanding of gene regulatory relationships and inflammatory mechanisms in the immune cells of COVID-19 patients and lay the foundation for the discovery of new diagnostic markers for COVID- 19. However, at present, there are still few genomic studies on peripheral blood leukocytes in patients with COVID-19, and the mechanism of the abnormal inflammatory response to SARS-CoV-2 infection is still not fully understood.…”
mentioning
confidence: 99%